OR16-03 Metabolic Effects Of Hypothalamic Pomc Neurons Generated Postnatally From Tanycytes On A Pomc Null Genetic Background - Gahlot, Surbhi (J Endocr Soc, 2020)
Hypothalamic proopiomelanocortin (POMC) neurons are an integral part of the central melanocortin system and regulate feeding and energy balance in vertebrates. Tanycytes are radial glial-like cells lining the third ventricle that contain a subpopulation of adult stem cells, which can differentiate under specific circumstances into glia and neurons, including POMC neurons. However, the capacity of these stem cell-derived neurons to fully mature and integrate into existing neural circuits of physiological relevance is unknown. This study systematically tested whether Pomc mRNA-positive cells newly generated from tanycyte precursors can differentiate into melanocortin-secreting POMC neurons, integrate into the normal anatomical projection pathways of these cells and rescue the obesity phenotype caused by the loss of Pomc expression in ArcPomc(fneo/fneo) mice. We generated an inducible compound genetic mouse model by crossing RaxCreERT2 with the Cre-dependent ArcPomc(fneo/fneo) and LSL-syp-tdTomato alleles. Rax is expressed exclusively in postnatal tanycytes, thereby limiting tamoxifen-induced recombination of the two floxed alleles by CreERT2 to tanycytes. As expected, tamoxifen treatment of the mice at age 4–5 wk recapitulated endogenous Rax expression 16 wk later as observed by red fluorescent tdTomato expression in all tanycytes. In addition, Cre recombinase-mediated deletion of the floxed-neomycin cassette from the neuronal enhancer region of the ArcPomc(fneo) alleles relieved their constitutive transcriptional silencing. Consequently, tamoxifen treatment consistently generated a significant number of newly generated POMC neurons from tanycytes (~10% of the POMC neurons in a WT mouse), identified by Pomc FISH and POMC/α-MSH immunofluorescence in the soma and established terminal projections to hypothalamic nuclei including the PVH and DMH involved in energy homeostasis. A subpopulation of these neurons also expressed the synaptophysin-tDTomato reporter. We performed serial body weight, food intake, body composition, oral GTT and insulin measurements with the RaxCreERT2/+, ArcPomc(fneo/fneo) mice and found no significant differences in any of these metabolic variables compared to untreated obese ArcPomc(fneo/fneo) mice. These data are consistent with previous studies from our lab suggesting that Pomc expression has to be at least ~30% of normal to mitigate the obesity phenotype in Pomc-null mice. In conclusion, we demonstrated that tanycytes are capable of generating mature Pomc-expressing neurons in the hypothalamus of adult mice. However, we propose that determining the underlying mechanisms involved in the generation of hypothalamic POMC neurons from tanycytes and interventions to increase their number, might lead to a novel approach to treat obesity. Nothing to Disclose: SG, GW, RML, MJL